Reformulation - Damiš, Marko (knjige, 2022)
The CA2RE / CA2RE+ LJUBLJANA event is a part of the CA2RE+ Erasmus+ Strategic Partnership. It is the 5th of 6 Intensive Study Programmes for Doctoral Candidates within the Strategic Partnership running 2019-2022. The project is developed as a parallel and a trigger to the continuity of the CA2RE Conferences for Artistic and Architectural REsearch.